Molecular Engineering of Direct Activated NIR-II Chemiluminescence Platform for In Vivo Chemiluminescence-fluorescence Duplex Imaging - Zhongxiang Chen; Qian Li; Ying Wu; Jianyong Liu; Luntao Liu; Lichao Su; Rongrong Wu; Jibin Song (Nature Communications)
Abstract Chemiluminescence (CL) is a self-illuminating phenomenon fueled by chemical energy instead of extra excited light, which features superiority in sensitivity, signal-to-background ratios, and imaging depth. Strategies to synthesize a CL emission unimolecular skeleton in the second near-infrared window (NIR-II) and a unimolecular probe with direct duplex NIR-II [CL/fluorescence (FL)] emission are lacking. Here, we employ modular synthesis routes to construct a series of directly activated NIR-II CL emission unimolecular probes with a maximum emission wavelength of up to 1060 nm, and use them for real-time and continuous detection of the superoxide anion generated in acetaminophen induced liver injury in a female mice model under both NIR-II CL and NIR-II FL imaging channels. Thus, this study establishes a directly activatable NIR-II CL emission unimolecular skeleton, validating the scalability of this duplex NIR-II CL/FL imaging platform in bioactive molecule detection and disease diagnosis.